Pengembangan Sistem Pendukung Keputusan Untuk Menentukan Distributor IT Menggunakan Pendekatan ROC dan COPRAS - Nurhayati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Distributors play a strategic role in the supply chain, particularly in the information technology (IT) industry, as intermediaries between IT product manufacturers and consumers. Selecting the right distributor is crucial to ensuring product quality, delivery efficiency, and reliable after-sales services. However, manual processes in distributor selection often face challenges such as subjectivity, inefficiency, and the complexity of criteria. This study developed a web-based Decision Support System (DSS) utilizing the Rank Order Centroid (ROC) and Complex Proportional Assessment (COPRAS) methods to support systematic and objective evaluation and selection of distributors. ROC was employed to determine the weights of criteria based on priorities, while COPRAS was used to evaluate alternatives and rank them according to utility values. The case study revealed that CompNet (A5) was the best distributor with the highest utility value of 100%, followed by Mikom (A2) (94.91%), Datascrip (A1) (91%), Astrindo (A3) (83.29%), and VSTecs (A4) (82.72%). The system produced automated results consistent with manual calculations, demonstrating its accuracy and reliability. The black-box testing also confirmed that all system features functioned as specified. This research contributes to the development of a web-based DSS for IT distributor selection by integrating the ROC and COPRAS methods, which are relevant for multi-criteria decision-making and practical for corporate implementation.